2021
DOI: 10.1002/uog.23135
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of smart tracheal occlusion device in diaphragmatic hernia lamb model

Abstract: In fetal lambs with diaphragmatic hernia (DH), tracheal occlusion using the 'smart' tracheal occlusion (Smart-TO) device is effective and safe. The occlusion could be effectively reversed non-invasively and the deflated intact balloon was expelled spontaneously out of the fetal upper airways. What are the clinical implications of this work? This study proves the efficacy and safety of the Smart-TO balloon in the DH lamb model. This study is the last preclinical step before a first-in-woman study. Clinical use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
(61 reference statements)
1
13
0
Order By: Relevance
“…The dimensions of the Smart-TO balloon and material (latex) are the same as the Goldbal2® balloon. For this reason, it is anticipated that the Smart-TO will induce similar lung growth compared to the Goldbal2® balloon, as previously demonstrated in preclinical studies [12, 17]. Additional outcome measurements include the occurrence of membrane rupture and preterm delivery, which is consistently reported in all FETO series.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The dimensions of the Smart-TO balloon and material (latex) are the same as the Goldbal2® balloon. For this reason, it is anticipated that the Smart-TO will induce similar lung growth compared to the Goldbal2® balloon, as previously demonstrated in preclinical studies [12, 17]. Additional outcome measurements include the occurrence of membrane rupture and preterm delivery, which is consistently reported in all FETO series.…”
Section: Discussionmentioning
confidence: 75%
“…The dimensions of the Smart-TO balloon and material (latex) are the same as the Goldbal2® balloon. For this reason, it is anticipated that the Smart-TO will induce similar lung growth compared to the Goldbal2® balloon, as previously demonstrated in preclinical studies [12,17].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Surgeons continue to optimize FETO by developing new surgical techniques and devices that improve outcomes. One recent example is the development of a smart tracheal occlusion device that not only autoregulates lung fluid egression to optimize lung growth, but also eliminates the need for a second fetoscopic procedure to deflate the balloon ( 112 ). In the same vein, another group has developed a degradable hydrogel for tracheal occlusion that would also obviate the need for a second surgery ( 113 ).…”
Section: Discussionmentioning
confidence: 99%
“…After deflation, the balloon is either swallowed by the fetus or exits the mouth into the amniotic fluid. Tests in large animal models confirmed that this device has similar occlusive and tracheal side effects as the currently used “Goldbal” balloon (Balt, Montmorency, France) and that it spontaneously releases after MRI exposure 41‐43 . In Leuven and Paris, we have moved to the “first‐in‐human" trial, aiming to demonstrate the feasibility to deflate the balloon by exposing the fetus to the magnetic field generated by a clinical MRI scanner.…”
Section: Improvements In Fetal Surgerymentioning
confidence: 97%